2009
DOI: 10.1107/s1600536808043419
|View full text |Cite
|
Sign up to set email alerts
|

2,4,4-Tris(benzylsulfanyl)-1,1-dichloro-3-nitrobuta-1,3-diene

Abstract: In the title compound, C25H21Cl2NO2S3, the three phenyl rings are inclined to each other at dihedral angles of 68.4 (1), 79.5 (1) and 37.0 (1)°.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…X-Ray structural analysishave shown that the nitrodiene 4g is Eisomer with a non-planar and close to cisoid configuration. Some E-and Z-isomer thiosubstitue nitrodiene compounds have been reported [34][35][36][37][38][39][40][41] that the observed values in compound 4g is consistent with the corresponding values in these similar compounds.…”
Section: Crystallographic Measurementsmentioning
confidence: 67%
“…X-Ray structural analysishave shown that the nitrodiene 4g is Eisomer with a non-planar and close to cisoid configuration. Some E-and Z-isomer thiosubstitue nitrodiene compounds have been reported [34][35][36][37][38][39][40][41] that the observed values in compound 4g is consistent with the corresponding values in these similar compounds.…”
Section: Crystallographic Measurementsmentioning
confidence: 67%
“…According to a US patent, some thio-substituted dienes also exhibit high biological activity such as insecticide, herbicide and fungicide 2 .In recent years, certain mono-, di-, tris(thio) substituted compounds were obtained from the reactions of nitrodienes with thiols and dithiols [3][4][5][6][7][8][9] . There are some reports on the crystal structure of these compounds [10][11][12][13][14][15][16] . The oxidation reaction of organo sulphur compounds has been the focus of great interest recently in biochemistry and in industrial processes 17 .…”
mentioning
confidence: 99%